SR 121787, a New Orally Active Fibrinogen Receptor Antagonist - Savi, Pierre; Badorc, Alain; Lalé, Alain; Bordes, Marie-Françoise; Bornia, Josette; Labouret, Catherine; Bernat, André; Cointet, Paul de; Hoffmann, Peter; Maffrand, Jean-Pierre; Herbert, Jean-Marc (Thrombosis and Haemostasis, 1998)
The aim of this study was to describe the pharmacological properties of SR 121787, a new antiaggregating drug which is metabolized in vivo into SR 121566, a potent non-peptide antagonist of Gp IIb/IIIa. In vitro, SR 121566 antagonized the binding of [125I]-fibrinogen (IC50 = 19.8 ± 6.3 nM) and of [125I]-L-692,884, an RGD-containing peptide (IC50 = 291 ± 96 nM) to activated human platelets. SR 121566 inhibited the aggregation of human platelets induced by ADP, collagen, thrombin, arachidonic acid and PAF at concentrations lower than 0.1 μM. Adhesion of human platelets to adhesive proteins was inhibited by SR 121566 (IC50 = 40.3 ± 2.5 nM) only when Gp IIb/IIIa and fibrinogen were involved. No effect was found with regard to other adhesive proteins and/or other integrins. SR 121787 demonstrated a potent and sustained antiaggregating effect when administered intravenously to baboons at a dose 50 μg/kg, and eight hours after the administration of 100 μg/kg, ADP-induced aggregation was still strongly inhibited (more than 80%). A single oral administration of 2 mg/kg of SR 121787 produced a nearly complete inhibition of platelet aggregation for up to 8 h (ED50 at 8 h = 193 ± 20 μg/kg), a significant residual antiaggregating activity being still observed 24h after the administration. When administered orally to rabbits, SR 121787 exhibited a potent antiaggregating (ED50 = 2.3 ± 0.3 mg/kg) and antithrombotic activity in an arterio-venous shunt thrombosis model (ED50 = 10.4 ± 0.8 mg/kg). After oral and IV administration, SR 121787 was well tolerated suggesting that SR 121787, the most potent and long lasting orally active Gp IIb/IIIa antagonist described to date, is a promising antithrombotic compound.